Low dose Adenoviral Vammin gene transfer induces myocardial angiogenesis and increases left ventricular ejection fraction in ischemic porcine heart - Järveläinen, Niko; Halonen, Paavo J.; Nurro, Jussi; Kuivanen, Antti; Pajula, Juho; Tarkia, Miikka; Grönman, Maria; Saraste, Antti; Laakkonen, Johanna; Toivanen, Pyry; Nieminen, Tiina; Rissanen, Tuomas T.; et al. (Springer Nature, 2025)
This preliminary study investigated if VEGFR-2 selective adenoviral Vammin (AdVammin) gene therapy could induce angiogenesis and increase perfusion in the healthy porcine myocardium. Also, we determined using a clinically relevant large animal model if AdVammin gene therapy could improve the function of a chronically ischemic heart. Low doses of AdVammin (dose range 2 x 109-2 x 1010 vp) gene transfers were performed into the porcine myocardium using an endovascular injection catheter. AdCMV was used as a control. The porcine model of chronic myocardial ischemia was used in the ischemic studies. The AdVammin enlarged the mean capillary area and stimulated pericyte coverage in the target area 6 days after the gene transfers. Using positron emission tomography 15O-radiowater imaging, we demonstrated that AdVammin gene therapy increased perfusion in healthy myocardium at rest. AdVammin treatment also increased ejection fraction at stress in the ischemic heart, as detected using left ventricular cine angiography. In addition, we demonstrated successful in vivo imaging of enhanced angiogenesis using [68Ga]NODAGA-RGD peptide. However, AdVammin also increased tissue permeability and was associated with significant pericardial fluid accumulation, limiting AdVammin's therapeutic potential and emphasizing the importance of correct dosage.